Development of student worksheets based on the PBL model to improve students' critical thinking ability - Dewi Nurhasanah Nasution; Reh Bungana Boru Perangin-angin; Wildansyah Lubis (Himpunan Pengembang Kurikulum Indonesia, 2026)
In the 21st century, students need to possess 4C skills: critical thinking, collaboration, communication, and creativity. In improving students' critical thinking skills through the learning process, it is highly dependent on learning resources, for example Student Worksheets (LKPD). This study aims to develop and determine the feasibility, practicality, and effectiveness of Problem Based Learning (PBL)-based LKPD developed for the critical thinking skills of fourth-grade students of SD Negeri 101775 Sampali. This study is a Research and Development (RnD) study using the ADDIE model approach, namely Analysis, Design, Development, Implementation, and Evaluation. The research instruments used are observation, questionnaires and critical thinking ability tests. The results of the study indicate that PBL-based LKPD is suitable for use, based on the feasibility test of LKPD products by the validator. Based on teacher and student responses, PBL-based LKPD is very practical to use with the results of responses obtained by two teachers and the results of student responses. PBL-based LKPD is effective to use with the criteria of